If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5r + -2r + -1s = -16 Combine like terms: -5r + -2r = -7r -7r + -1s = -16 Solving -7r + -1s = -16 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add 's' to each side of the equation. -7r + -1s + s = -16 + s Combine like terms: -1s + s = 0 -7r + 0 = -16 + s -7r = -16 + s Divide each side by '-7'. r = 2.285714286 + -0.1428571429s Simplifying r = 2.285714286 + -0.1428571429s
| Z^4-8z^2+16=0 | | ln(5-x)+ln(2-x)=ln(28-4x) | | 0=3x^2+6xy | | z^5-5z^3-36z=0 | | 6x*-4=-17x | | 6x*-4= | | 75x^2+30x+3= | | 3.6x^2-13.8x+9.2=0 | | 15x+95=12x+123 | | ln(6x)=14 | | 10x^2+15x=-1 | | -40x/32 | | 4x+2x=3+8 | | w=36-8w | | 14y=25+9y | | 11(n-8)-5=54 | | (x+50)squared= | | 0.1x+35x+15000= | | cosx=4-x^2 | | 6x+30+2x+40=90 | | 2(2y+5)=3(y+5) | | 5y-1=4y | | 5y-12=y | | -3(9y+2)=2(4y-7) | | Sqrt(36(x^6)(y^4))=0 | | 30x+15=4(6x+3)+6x+3 | | 7-(-2k+4)-6=7k-20 | | 14y+19=2y+127 | | (2x-1)/3=4 | | (2x-1)/=4 | | 3y-14=y | | (2x-1)/34 |